Socio-Economics of Childhood Pulmonary Tuberculosis with Adult Tuberculosis Household Contacts in Daerah Istimewa Yogyakarta Province - Asyary, Al; Junadi, Purnawan; Purwantyastuti, Purwantyastuti; Eryando, Tris (Makara Journal of Health Research, 2017)
Background: Since the tuberculosis (TB) disease in children constitutes a global health problem that has long been neglected, this study sought to predict socioeconomic factors as public-health determinants that could protect children who were exposed to TB in their household. Method: A case-control study of 132 children (under 14 years old) who shared their household with adults suffering from pulmonary TB was conducted in the Province of Daerah Istimewa Yogyakarta. This study consisted of an interview and anthropometry measurement for the controls screening test, while the cases were monitored by pediatricians with a scoring system childhood TB diagnosis from the secondary hospital database. A multiple logistic regression was used to analyze the results. Results: A healthy housing condition, predicted by a naturally illuminated luminary bedroom prevented the incidence of the childhood TB disease (p = 0.043) even if exposed to adult TB in their environment (p = 0.775). Conclusions: Healthy housing factors with good sunlight protected children especially at the early stage, when there were active pulmonary TB adult household contacts. Ventilation and morning sunlight facilitated air circulation, vitality and the body’s immune system towards TB protection.